Necrotizing 'sarcoidal' angiitis and granulomatosis of the lung. Issue 3 (June 1976) - Stephen, J G; Braimbridge, M V; Corrin, B; Wilkinson, S P; Day, D; Whimster, W F
Abstract : A case of necrotizing sarcoid angiitis and granulomatosis (NSG) presenting as a peripheral lung 'tumour' in a 63-year-old man is recorded, and the clinical and pathological features are compared with those of Liebow's original cases. Resection may be avoided if the diagnosis is made by biopsy as the disease is possibly steroid responsive and the prognosis appears favourable. The aetiology is obscure but an immune disturbance is suspected.